2014
DOI: 10.3842/sigma.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of an Inverting Tippe Top

Abstract: Abstract. The existing results about inversion of a tippe top (TT) establish stability of asymptotic solutions and prove inversion by using the LaSalle theorem. Dynamical behaviour of inverting solutions has only been explored numerically and with the use of certain perturbation techniques. The aim of this paper is to provide analytical arguments showing oscillatory behaviour of TT through the use of the main equation for the TT. The main equation describes time evolution of the inclination angle θ(t) within a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This proposition states that if λ > λ thres , so that TT is inverting, then the minimum z min of V(z, D(t), λ) is moving from an ǫ-neighborhood of z = 1 to an ǫ-neighborhood of z = −1. In [8] it has also been shown that the time of passage for θ(t) between two turning points has a uniform bound…”
Section: Corollarymentioning
confidence: 99%
See 2 more Smart Citations
“…This proposition states that if λ > λ thres , so that TT is inverting, then the minimum z min of V(z, D(t), λ) is moving from an ǫ-neighborhood of z = 1 to an ǫ-neighborhood of z = −1. In [8] it has also been shown that the time of passage for θ(t) between two turning points has a uniform bound…”
Section: Corollarymentioning
confidence: 99%
“…A rigorous approach showing oscillatory behaviour of TT inverting solutions has been proposed in [7,8,10]. It is based on an integrated form of TT equations that are equivalent to the Euler angle equations and to the dynamical Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation